IMPLEMENTASI KUALITAS PELAYANAN PUBLIK PADA BADAN PELAYANAN PERIZINAN TERPADU DI KOTA PALU - Armelia, Nita (Katalogis, 2016)
The problem of this study was how the public service quality of and what factors influencing Palu City Board for Integrated Licensing Services? The purpose of this study was to determine the real situation, to get an overview of various issues that arise, and to identify factors that influence the public service quality at Palu City Board for Integrated Licensing Services. The type of research used was qualitative descriptive research. The research was conducted at Palu City Board for Integrated Licensing Services. The informants of this study assigned purposively were the people of Palu City as the consumers of Palu City Board for Integrated Licensing Services and the apparatuses of Palu City Board for Integrated Licensing Services as the key informants. Data were collected through observations, interviews, and documentations. The results showed that the public services quality at Palu City Board for Integrated Licensing Services had run well, the organizational structure had run as expected, as well as the ability of the apparatuses had been quite good, and the service system had been already good. The factors that influenced the public services quality at Palu City Board for Integrated Licensing Services were the organizational structure, the apparatuses ability, and the service system.